Secondary foreign policy in local international relations peace-building and reconciliation in border regions - Klatt, Martin 1964-; Wassenberg, Birte (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2018)
This book collects eight case studies on how regional and local government and non-political stakeholders can contribute to reconciliation, peace-building and cooperation across borders. The chapters were originally published in a special issue ofRegional & Federal Studies."--Provided by publisher